Evaluation of Mucosal Healing in Ulcerative Colitis by Fecal Calprotectin vs. Fecal Immunochemical Test: A Systematic Review and Meta-analysis - Hu, Tingpeng; Zhang, Zhimei; Song, Fusheng; Zhang, Wenguang; Yang, Jun (Turkish Journal of Gastroenterology, 2023)
Mucosal healing has been considered a treatment goal for patients with inflammatory bowel disease. To compare the accuracy of fecal immunochemical test and fecal calprotectin in the judgment of mucosal healing in ulcerative colitis, a meta-analysis was performed. We searched the PubMed, Cochrane Library, Web of Science, and Embase for the studies on fecal immunochemical test and fecal calprotectin predicting mucosal healing in ulcerative colitis. The comprehensive sensitivity, specificity, diagnostic odds ratio, positive likelihood ratio, and negative likelihood ratio were calculated to evaluate the accuracy. By analyzing 22 publications, we found that the combined sensitivity and specificity of fecal immunochemical test were 0.87 (95% CI, 0.80-0.92) and 0.73 (95% CI, 0.62-0.81), respectively. The combined sensitivity and specificity of fecal calprotectin were 0.76 (95% CI, 0.70-0.80) and 0.80 (95% CI, 0.76-0.84), respectively. The area under the curve values of the fecal immunochemical test and fecal calprotectin summary receiver operating characteristic (SROC) curves were 0.88 and 0.85, respectively. Consequently, fecal immunochemical test had higher sensitivity in predicting mucosal healing in ulcerative colitis patients, while fecal calprotectin had higher specificity. Compared with fecal calprotectin, fecal immunochemical test was more accurate in judging mucosal healing in ulcerative colitis. Cite this article as: Hu T, Zhang Z, Song F, Zhang W, Yang J. Evaluation of mucosal healing in ulcerative colitis by fecal calprotectin vs. fecal immunochemical test: A systematic review and meta-analysis. Turk J Gastroenterol. 2023;34(9):892-901.